Cathedralizing Nature, Ecologizing Sacred Grounds: A Case Study from Sápmi on the Norwegian Side - Kraft, Siv Ellen (Journal for the study of religion, nature and culture, 2025)
Can the past save the future? Can sacredness protect mountains? Do mountains have a say? The case of Davvi Wind park versus Rásttigáisá in Northern Norway offers a window into "green shift" complexities in indigenous landscapes. Elements include a sacred mountain, a planned wind park, and a new-old faith organisation, founded to protect this mountain and the sacred geographies of Sápmi. Connections to nature were never lost in this region although due to missionization and colonialism connections to the ancestral Sámi religion have been partly lost. To ecologize, in this context, is to protect and (re)connect; to reclaim faithways and thereby save lifeways and the landscapes that sustain them. Cathedralizing and indigenizing constitute modes of proceeding, along with middleground sacredness, beyond religion and the secular. While anchored in ancestral religion in the past, the sacred mountains of Sápmi are also legal entities with the potential power to move faith and protect these sacred grounds.